Pelvic Rocking and Birth Ball Interventions to Reduce Duration of Second Stage of Labor and Improve Neonatal APGAR Scores - Misbawati, Misbawati; Ahmad, Mardiana; Sudirman, Jumrah; Tamar, Tamar; Husin, Farid (Journal of Neonatal Surgery, 2025)
Prolonged second-stage labor is a critical obstetric issue that increases the risk of maternal and neonatal complications, including postpartum hemorrhage and neonatal asphyxia. These complications can lead to low APGAR (Appearance, Pulse, Grimace, Activity, Respiration) scores, sepsis, and perinatal mortality. In Indonesia, 12–15% of labor cases are reported to be prolonged, highlighting the need for effective interventions. This study aimed to analyze the effects of pelvic rocking exercises and birth ball use on the duration of the second stage of labor and neonatal APGAR scores. This quasi-experimental study employed a post-test-only control group design and involved 40 primigravida mothers selected through purposive sampling from several health facilities in Gowa Regency, including TPMB Hj. Kasmawati, Hj. Hamsinah, Hj. Kumala Ratna, Bajeng Health Center, and Bontonompo II Health Center. Participants were divided into intervention and control groups. The intervention group received pelvic rocking exercises and birth ball therapy during labor. The results showed a significant reduction in the duration of the second stage of labor in the intervention group compared to the control group (Mann–Whitney test, p = 0.000). However, there was no significant difference in neonatal APGAR scores at 5 minutes (p = 0.673) and 10 minutes (p = 0.277) between the groups. While pelvic rocking and birth ball interventions effectively shortened the second stage of labor through biomechanical and neuroendocrine mechanisms, they did not significantly influence neonatal outcomes as measured by APGAR scores, possibly due to other overriding clinical factors.